Serious fun at a Jewish community summer camp : family, Judaism, and Israel - Rothenberg, Celia, 1970- (Lexington Books, 2016)
"This book is an ethnographic and historical study of Camp Ben Frankel (CBF), a Jewish community summer camp in southern Illinois. It reveals the significance of song and Jewish "family" for the camp experience and shows how small camps can contribute to our understanding of American Jews and how their Judaism and Zionism have changed over time."--Provided by publisher